Peningkatan Kapasitas Paru Dengan Metode Ballon Blowing Relaxation Pada Perokok Aktif - Nian Afrian (Jurnal Kesehatan, 2023)
The maximum/total volume of air that can be released from the lungs is its vital capacity. Everyone's lung vital capacity is susceptible to a variety of different causative causes. One of the factors affecting lung vital capacity is smoking behavior. Smoking can hasten the deterioration of lung function and alter the respiratory system's anatomy, structure, and function. This study aimed to investigate the impact of balloon blowing relaxation on smokers' lung vital capacity. This study's design was pre-experimental, and it used purposive sampling to select a sample size of 30 respondents. According to the study's findings, the majority of respondents were male, between the ages of 45 and 50, did not frequently exercise, had a majority of high school degrees, and worked in the private sector. The majority of smoking history spans 10 years, with a total of 11–20 cigarettes smoked throughout that time. According to the findings of data analysis utilizing the Paired T-Test, balloon blowing relaxation had an impact on active smokers' lung vital capacity. The diaphragm and rib muscles can be raised by the intercostal muscles with the use of the balloon blowing relaxation technique. It is anticipated that the balloon blowing relaxation technique would be used as an option to increase the lung vitality of active smokers.